The politics of domestic gas: The Sasol natural gas deals in Mozambique. Issue 4 (November 2020) - Salimo, Padil; Buur, Lars; Macuane, Jose Jaime
Highlights: How access to revenues and rents related to the Sasol natural gas project has evolved. How the ruling Frelimo elite in Mozambique engaged creatively with liberal reforms. Sasol´s first and second phase gas deals in Mozambique. How do formal contracts actually allow rent-seeking by ruling elites under pressure to secure revenues and rents for political survival. Fiscal regime´s helps us understand the dynamics related to rent seeking and deal-making during the formative years of the gas sector in Mozambique. Abstract: This article explores the ways in which the ruling Frelimo elite in Mozambique engaged creatively with the opportunities and constraints created by Sasol's Pande and Temane natural gas project as they have evolved from the early 2000s until today. This is a period that has seen ruling-elite actors become involved in various projects related to the production of electricity from 'domestic natural gas'. We argue that focusing on the initial gas investment and how it evolved over time makes it possible to understand the dynamics related to deal-making during the formative years when the Mozambican petroleum industry was reformed by separating its commercial and regulatory functions. More specifically we explore how access to revenues and rents related to natural gas projects have evolved. We point out that, although the Pande-Temane gas project has increased revenue generation, most of the gas was sold to the South African major, Sasol, for a very low amount of revenue during the first phase of the project. Revenues from the second phase, starting in 2012, did not increase dramatically, even though Mozambique acquired access to 50% of the gas from the extension of the pipeline and increased production. Instead, the increase in domestic gas allocated to the Mozambican market involved the allocation and distribution of gas to private companies at special prices, most of which were controlled by dominant ruling-elite factions under the Chissano and Guebuza governments. We argue that this has been the main mechanism for the transfer of rents from the public to the private domain.